Varying the Directionality of Protein Catalysts for Aldol and Retro‐Aldol Reactions. (11th November 2021) - Fujioka, Toshifumi; Numoto, Nobutaka; Akama, Hiroyuki; Shilpa, Kola; Oka, Michiko; Roy, Prodip K.; Krishna, Yarkali; Ito, Nobutoshi; Baker, David; Oda, Masayuki; Tanaka, Fujie
Abstract: Natural aldolase enzymes and created retro‐aldolase protein catalysts often catalyze both aldol and retro‐aldol reactions depending on the concentrations of the reactants and the products. Here, we report that the directionality of protein catalysts can be altered by replacing one amino acid. The protein catalyst derived from a scaffold of a previously reported retro‐aldolase catalyst, catalyzed aldol reactions more efficiently than the previously reported retro‐aldolase catalyst. The retro‐aldolase catalyst efficiently catalyzed the retro‐aldol reaction but was less efficient in catalyzing the aldol reaction. The results indicate that protein catalysts with varying levels of directionality in usually reversibly catalyzed aldol and retro‐aldol reactions can be generated from the same protein scaffold. Abstract : Protein catalysts with varied levels of directionality in usually reversibly catalyzed aldol and retro‐aldol reactions were generated using the same protein scaffold.